Understanding Human Development / Biological, Social and Psychological Processes from Conception to Adult Life - Thornton Stephanie (Palgrave Macmillan, 2008)
The author critically reviews research on human development from the earliest studies to the theories and issues of the 21st century, including recent breakthroughs in neuropsychology, cross-cultural psychology and in the application of dynamic systems theory. Studying Human Development, The Beginning of Life, Bodies and Brains, Infrant Minds: Perception and Inference and Understanding in the First 18 Months, Growing Emotions: Social and Personal Development in the First 18 Months, Cognitive Development from Infancy from Infancy to Adulthood, Language, Reasoning and Conceptual Understanding, Memory and Problem Solving and Mechanisms of Cognitive Development, Individual Differences in Cognition, Prosocial and Antisocial Behavior, A Final Comment, Toward a New View of Development, References, Name and Subject Index.